The Association between Blood Glucose Control Measured with Serum Hna1c Level with Peroneal Motor Nerve Conduction Velocity in Patients with Type 2 Diabetes Mellitus with Polyneuropathy - Muhammad Hamdan1, Raini Wisnujono1 , Mudjiani Basuki1, Fidiana, Fadil1, Intan Sudarmadi1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background and Objective. The poor control of blood glucose levels in patients with diabetes mellitus is a major risk factor from various complications of diabetes mellitus, such as polyneuropathy. One of the nerves that are often affected in the case of diabetic neuropathy is the peroneal nerve. This study aimed to determine the association between blood glucose level control measured with serum hemoglobin A1c (HBA1c) levels with peroneal motor nerve conduction velocity in type 2 diabetes mellitus patients with polyneuropathy. Methods. The study was conducted on diabetic neuropathy patients who fulfilled inclusion and exclusion criteria in neurology unit and diabetes unit Dr. Soetomo General Hospital Surabaya on a consecutive basis from February to July 2013. The serum HbA1c level and nerve conduction velocity in peroneal motor nerve were examined; then, the results were grouped into two groups which were serum HbA1c <7% and ?7% and NCV in normal and low peroneal motor nerve Results. There were 26 subjects, consisting of 6 subjects with serum HbA1c <7% and 20 subjects with serum HbA1c ? 7%. There was an association between blood glucose level control measured by serum HbA1c levels and NCV in peroneal motor nerve with statistical significance of p = 0.0018 (Odd ratio 15; 95% IK 1.397 - 161.045). Conclusion. There was an association between blood glucose level control measured by serum HbA1c levels with NCV in peroneal motor nerve in type 2 diabetes mellitus patients with polyneuropathy